2018
DOI: 10.1038/s41598-018-30616-1
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial fatty acid uptake through CD36 is indispensable for sufficient bioenergetic metabolism to prevent progression of pressure overload-induced heart failure

Abstract: The energy metabolism of the failing heart is characterized by reduced fatty acid (FA) oxidation and an increase in glucose utilization. However, little is known about how energy metabolism-function relationship is relevant to pathophysiology of heart failure. Recent study showed that the genetic deletion of CD36 (CD36KO), which causes reduction in FA use with an increased reliance on glucose, accelerates the progression from compensated hypertrophy to heart failure. Here, we show the mechanisms by which CD36 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 36 publications
(64 reference statements)
0
67
0
1
Order By: Relevance
“…There are three possibilities for the decrease of FAs in the heart; the decrease in influx of FAs into the heart, the increase in consumption, and the dilution of total FAs. Since it has been reported that FA uptake into the hypertrophied heart was inhibited by various factors such as the increase of ketone bodies and the decrease of FA transporters' expressions 42,43 , the impairment of FA uptake might be a reason for the decrease of FAs in the heart. On the other hand, the second reason may be not the case, because there are reports indicating that the consumption of FAs is decreased in the pathological heart due to the impairment of mitochondrial function 7,44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…There are three possibilities for the decrease of FAs in the heart; the decrease in influx of FAs into the heart, the increase in consumption, and the dilution of total FAs. Since it has been reported that FA uptake into the hypertrophied heart was inhibited by various factors such as the increase of ketone bodies and the decrease of FA transporters' expressions 42,43 , the impairment of FA uptake might be a reason for the decrease of FAs in the heart. On the other hand, the second reason may be not the case, because there are reports indicating that the consumption of FAs is decreased in the pathological heart due to the impairment of mitochondrial function 7,44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…In the heart, CD36 and PPARγ form a positive feedback loop. CD36 at the cell membrane facilitates longchain fatty acid entry, fatty acids are natural PPARγ ligands and activate PPARγ, and this leads to PPARγ/RXR binding at the PPRE in the CD36 promoter producing increased CD36 expression [55,56]. In contrast to lowered PGC1α expression associated with diabetes described above, diabetic humans [57] and rodents [58,59] have elevated CD36 expression.…”
Section: Can Target Engagement Of Pparγ By Pioglitazone Be Detected Imentioning
confidence: 99%
“…They identified a cell type in human oral carcinomas with the following properties: (1) slow-cycling, (2) CD44-bright, (3) low expression of mesenchymal genes, (4) ability to initiate metastasis in mouse models and (5) high expression of the fatty acid receptor CD36. CD36 is a membrane protein on the surface of many mammalian cells that imports fatty acids (Yang et al, 2018[ 34 ]; Umbarawan et al, 2018[ 31 ]; Son et al, 2018[ 28 ]). CD36 has been shown to be critical for supply with fatty acids and for maintenance of energy metabolism under numerous conditions (Wen et al, 2017[ 33 ]; Chen et al, 2016[ 5 ]; Nakatani et al, 2015[ 21 ]; le Foll et al, 2015[ 15 ], 2013[ 14 ]).…”
Section: mentioning
confidence: 99%